Cadmium (Cd) Concentration in Mudskipper, Water and Sediment in the Mangrove Area of Pemangkat West Kalimantan - Nurhidayanti, Nurhidayanti; Sofiana, Mega Sari Juane; Safitri, Ikha (Sam Ratulangi University, 2023)
Mangrove vegetation has a wide range of distribution on the Indonesian coast, including Pemangkat, Sambas Regency, and West Kalimantan. Near this area, there are various activities, such as industrial, fishing, and shipping which are possible sources of heavy metal pollution. Water pollution caused by heavy metals is one of the serious problems. This condition can reduce water quality and has an impact on aquatic organisms. Monitoring of water quality needs to be done to reduce health problems and maintain the stability of aquatic ecosystems. Mudskipper (Boleophthalmus sp.) can be used as a bioindicator due to its ability to accumulate heavy metals from the environment, especially in mangrove areas. Heavy metal such as cadmium (Cd) is difficult to decompose and toxic to the environment and biota. This heavy metal pollution may originate from port and fisheries activities. The aim of this study was to determine the Cd content in the Mudskipper, waters, and sediment samples. Sampling was carried out at two stations. Analysis of the Cd content was done using Atomic Absorption Spectrophotometry (AAS). The result showed that concentrations of Cd in the waters and sediment samples were above the threshold. Meanwhile, the Cd level in Mudskipper flesh was still below the maximum limit. Keywords: heavy metal, cadmium (Cd), mudskipper, Pemangkat, West Kalimantan